Complexidade ambiental: efeitos na aprendizagem e agressividade do Peixe-donzela (Stegastes fuscus) - Pinto, Thalles da Silva (2019)
Dusky damselfish (Stegastes fuscus) is a endemic reef fish from Brazil that occurs at coast of the RN until SC. This species presents a agonistic behavior in defending your territory against intra and interspecific animals that transit or compete for resources, being considered a "key-specie" in the reefs in which occurs. S. fuscus plays a important role in regulating the agonistic relationships among the various species that make up reef community. Due to the high anthropogenic impact the reef environments have been modified in terms of temperature, pH, oxygen and structural complexity. Research that relates changes in temperature and habitat structure of animals with behavioral and learning alterations can help to understanding ecological consequences of these impacts and suggest more effective conservation alternatives. This study aimed to better understanding how global climate change can influence changes in the agressiveness, territoriality and learning of S. fuscus. The objective of this work was to test if the environmental complexity and water temperature influence the learning and aggressiveness of S. fuscus. All animals were collected on Pirambúzios Beach, transferred to the laboratory and placed in stock tanks. For experiment 1, animals were divided into: EE group (n=11) habitat consisting of an tank with bottom and walls covered with gravel substrate adhesive, shelter and artificial plant and group "BE" (n=09) habitat consisting of an tank without additional items. After 34 days under these conditions, time spent in each area and latency to reach the target area were quantified. For experiment 2, beyond to the complexity levels, there was also a temperature regime, as follows: Group "28B" (n=09) barren habitat at 28ºC, "28C" group (n=12), complex habitat at 28°C, group "34B" (n=09) barren habitat at 34°C and group "34C" (n=06) complex habitat at 34°C. After 30 days under these conditions, animals were submitted to mirror test, being filmed before (5min) and after (5min) exposure to the mirror, being verified swimming velocity, immobility time, time spent in each quadrants and frequency of agonistic displays in the two moments. Our results suggest that, in a future scenario, S. fuscus will have higher energetic costs caused not only by increase of temperature but also by physiological changes and its behavioral pattern.